MucoRice-CTB line 19A, a new marker-free transgenic rice-based cholera vaccine produced in an LED-based hydroponic system - Yuki, Yoshikazu; Kurokawa, Shiho; Sugiura, Kotomi; Kashima, Koji; Maruyama, Shinichi; Yamanoue, Tomoyuki; Honma, Ayaka; Mejima, Mio; Takeyama, Natsumi; Kuroda, Masaharu; Kozuka-Hata, Hiroko; Oyama, Masaaki; et al. (Frontiers in Plant Science, 2024)
We previously established the selection-marker-free rice-based oral cholera vaccine (MucoRice-CTB) line 51A for human use by Agrobacterium-mediated co-transformation and conducted a double-blind, randomized, placebo-controlled phase I trial in Japan and the United States. Although MucoRice-CTB 51A was acceptably safe and well tolerated by healthy Japanese and U.S. subjects and induced CTB-specific antibodies neutralizing cholera toxin secreted by Vibrio cholerae, we were limited to a 6-g cohort in the U.S. trial because of insufficient production of MucoRice-CTB. Since MucoRice-CTB 51A did not grow in sunlight, we re-examined the previously established marker-free lines and selected MucoRice-CTB line 19A. Southern blot analysis of line 19A showed a single copy of the CTB gene. We resequenced the whole genome and detected the transgene in an intergenic region in chromosome 1. After establishing a master seed bank of MucoRice-CTB line 19A, we established a hydroponic production facility with LED lighting to reduce electricity consumption and to increase production capacity for clinical trials. Shotgun MS/MS proteomics analysis of MucoRice-CTB 19A showed low levels of α-amylase/trypsin inhibitor-like proteins (major rice allergens), which was consistent with the data for line 51A. We also demonstrated that MucoRice-CTB 19A had high oral immunogenicity and induced protective immunity against cholera toxin challenge in mice. These results indicate that MucoRice-CTB 19A is a suitable oral cholera vaccine candidate for Phase I and II clinical trials in humans, including a V. cholerae challenge study.